Ca2+ entry units in a superfast fish muscle - Kittelberger, J. Matthew; Franzini-Armstrong, Clara; Boncompagni, Simona (Frontiers in Physiology, 2022)
Over the past two decades, mounting evidence has demonstrated that a mechanism known as store-operated Ca2+ entry (SOCE) plays a crucial role in sustaining skeletal muscle contractility by facilitating Ca2+ influx from the extracellular space during sarcoplasmic reticulum (SR) Ca2+ depletion. We recently demonstrated that, in exercised fast-twitch muscle from mice, the incidence of Ca2+ entry units (CEUs), newly described intracellular junctions between dead-end longitudinal transverse tubular (T-tubule) extensions and stacks of sarcoplasmic reticulum (SR) flat cisternae, strictly correlate with both the capability of fibers to maintain contractions during fatigue and enhanced Ca2+ influx via SOCE. Here, we tested the broader relevance of this result across vertebrates by searching for the presence of CEUs in the vocal muscles of a teleost fish adapted for extended, high-frequency activity. Specifically, we examined active vs. inactive superfast sonic muscles of plainfin midshipman (Porichthys notatus). Interestingly, muscles from actively humming territorial males had a much higher incidence of CEU SR stacks relative to territorial males that were not actively vocalizing, strengthening the concept that assembly of these structures is dynamic and use-dependent, as recently described in exercised muscles from mice. Our results support the hypothesis that CEUs represent a conserved mechanism, across vertebrates, for enabling high levels of repetitive muscle activity, and also provide new insights into the adaptive mechanisms underlying the unique properties of superfast midshipman sonic muscles.